2018
DOI: 10.1158/1078-0432.ccr-17-2807
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating SOX2-potentiated Immune Escape of Head and Neck Squamous Cell Carcinoma with a STING-inducing Nanosatellite Vaccine

Abstract: The response rates of Head and Neck Squamous Cell Carcinoma (HNSCC) to checkpoint blockade are below 20%. We aim to develop a mechanism-based vaccine to prevent HNSCC immune escape. We performed RNA-Seq of sensitive and resistant HNSCC cells to discover central pathways promoting resistance to immune killing. Using biochemistry, animal models, HNSCC microarray, and immune cell deconvolution, we assessed the role of SOX2 in inhibiting STING-type I interferon (IFN-I) signaling-mediated antitumor immunity. To byp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
141
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 47 publications
(60 reference statements)
1
141
0
Order By: Relevance
“…The M2 cells repress the immune system (Genard et al, ), and their high existence within the tumor is associated with poor prognosis (B. Tan, Shi, et al, ). M1 cell recruitment and CTL production are the two simultaneous processes occurring in the tumor stroma, and the two phenomena are under the influence of IFN release to the TME (Y. S. Tan, Sansanaphongpricha, et al, ). CTLs within the tumor stroma send paracrine signals for changing macrophage polarity toward the antitumor M1 cells, and that the cells have negative cross‐talking with M2 cells in which a reduction in the number of M2 cells in the TME would cause a rise in the recruitment of CTLs to this milieu to exert antitumor immunity for regression of tumor.…”
Section: Ctl Cross‐talksmentioning
confidence: 99%
“…The M2 cells repress the immune system (Genard et al, ), and their high existence within the tumor is associated with poor prognosis (B. Tan, Shi, et al, ). M1 cell recruitment and CTL production are the two simultaneous processes occurring in the tumor stroma, and the two phenomena are under the influence of IFN release to the TME (Y. S. Tan, Sansanaphongpricha, et al, ). CTLs within the tumor stroma send paracrine signals for changing macrophage polarity toward the antitumor M1 cells, and that the cells have negative cross‐talking with M2 cells in which a reduction in the number of M2 cells in the TME would cause a rise in the recruitment of CTLs to this milieu to exert antitumor immunity for regression of tumor.…”
Section: Ctl Cross‐talksmentioning
confidence: 99%
“…The median follow-up at the time of analysis was 60.1 months. STING staining in HNSCC parenchyma and TME was independently defined and quantitated using Aperio ImageScope as we described previously (14,27). Upon removal of cores with insufficient tumor tissue, STING staining scores were available from 264 HNSCC specimens.…”
Section: Introductionmentioning
confidence: 99%
“…We found that STING expression in the tumor parenchyma remained a favorable prognosticator (P = 0.049), while the STING staining scores of the antigen-targeted cytotoxic T lymphocytes (CTLs); it remains unexplained why most HNSCCs are hypoimmunogenic despite the presence of high mutation burdens and the presentation of HPV-associated neoantigens (13). To explain this dichotomy, we recently demonstrated that HNSCC cells evade immune surveillance through suppression of the STING/IFN-I pathway, a key adaptive resistance mechanism that limits effector T cell expansion (14). IFN-I is produced by both cancer cells and antigen-presenting cells (APCs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well acknowledged that TAM mainly have an M2‐like phenotype. Clinical and experimental evidence has shown that TAM promote the development and progression of most tumor types (Ruffell and Coussens, ; Tan et al , ). There are many macrophages in OSCC tissues, and TAM are also believed to participate in OSCC progression (Kubota and Moriyama, ; Petruzzi et al , ; Sun et al , ).…”
Section: Introductionmentioning
confidence: 99%